Studying the Effect of Initial Conditions and System Parameters on the Behavior of a Chaotic Duffing System - Manhil, Maryan Mohamed; Jamal, Raied K. (Iraqi Journal of Physics, 2023)
This work presents a five-period chaotic system called the Duffing system, in which the effect of changing the initial conditions and system parameters d, g and w, on the behavior of the chaotic system, is studied. This work provides a complete analysis of system properties such as time series, attractors, and Fast Fourier Transformation Spectrum (FFT). The system shows periodic behavior when the initial conditions xi and yi equal 0.8 and 0, respectively, then the system becomes quasi-chaotic when the initial conditions xi and yi equal 0 and 0, and when the system parameters d, g and w equal 0.02, 8 and 0.09. Finally, the system exhibits hyperchaotic behavior at the first two conditions, 0 and 0, and the bandwidth of the chaotic signal becomes wider (2 a.u.) than in the first case. So, this system can be used in many physical applications, such as encrypting confidential information.